PENGARUH PENGETAHUAN, SIKAP DAN PERSEPSI TERHADAP PEMANFAATAN PELAYANAN DETEKSI DINI KANKER SERVIKS METODE INSPEKSI VISUAL ASAM ASETAT (IVA) DI PUSKESMAS TIGA JUHAR KABUPATEN DELI SERDANG - PEBRINAWANTI BR SARAGIH (LP2MTBM MAKARIOZ, 2018)
The problem of HIV/AIDS develops rapidly and becomes a threat globally. In order to restrain the spread of HIV/AIDS, the government provides health service facility with VCT (Voluntary Counseling and Testing) Clinic. Patients who did not revisit VCT Clinic of RSUP Haji Adam Malik, Medan, increased to 46.2% in 2011 and 62.4% in 2012.The objective of the research was to find out the influence of the factors of consumers and health service providers on the use of revisit to the special service center (Pusyansus) of VCT clinic at RSUP Haji Adam Malik, Medan. The research was an explanatory survey; it was conducted from July to September, 2013. The population was all 849 patients who had visited VCT clinic, and 90 of them were used as the samples. The data were gathered by conducting interviews with questionnaires and analyzed by using multiple logistic regression analysis at α = 0.05.The result of the research showed that, statistically, the factors of consumers (perception on illness, perception on VCT service, and belief in the result of clinical diagnosis) and health service providers (attitude of medical personnel, availability of medicines, and medical facility) had positive and significant influence on the use of revisit to VCT clinic of RSUP Haji Adam Malik, Medan. The perception on illness was the variable which had the most dominant influence on the revisit.It is recommended that the management of RSUP Haji Adam Malik, Medan: a) provide coordination with other agencies concerned such as the Health Service, KPA Province, KPAD, LSM, religious figures, and public figures to increase promotion about VCT through mass media, electronic, brochures/leaflets, and banners in order to prevent from the transmission of HIV/AIDS, b) develop doctors and counselors in communication technique with patients so that the effectiveness between doctors and patients in VCT clinic can be achieved, and counseling service to guarantee patients' confidentiality and comfort, and c) motivate health care providers to participate in training regularly in order to improve their skill and insight so that patients do not wait too long to do VCT.